Comparing Modeled and Measurement-Based Spherical Harmonic Encoding Filters for Spherical Microphone Arrays - Politis, Archontis; Gamper, Hannes (Proceedings of IEEE Workshop on Applications of Signal Processing to Audio and Acoustics (WASPAA), 2017)
Spherical microphone array processing is commonly performed in a spatial transform domain, due to theoretical and practical advantages related to sound field capture and beamformer design and control. Multichannel encoding filters are required to implement a discrete spherical harmonic transform and extrapolate the captured sound field coefficients from the array radius to the far field. These spherical harmonic encoding filters can be designed based on a theoretical array model or on measured array responses. Various methods for both design approaches are presented and compared, and differences between modeled and measurement-based filters are investigated. Furthermore, a flexible filter design approach is presented that combines the benefits of previous methods and is suitable for deriving both modeled and measurement-based filters.